Plasma Neutrophil-to-Lymphocyte Ratio on the Third Day Postburn is Associated with 90-Day Mortality Among Patients with Burns Over 30% of Total Body Surface Area in Two Chinese Burns Centers - Qiu L (Dove Medical Press, 2021)
Le Qiu,* Xu Jin,* Jun-Jie Wang,* Xu-Dong Tang,* Xiao Fang, Shi-Ji Li, Fei Wang, Xu-Lin Chen Department of Burns, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xu-Lin ChenDepartment of Burns, The First Affiliated Hospital of Anhui Medical University, 120 Wanshui Road, Hefei, Anhui, 230088, People’s Republic of ChinaTel +86-551-65908495 Email okcxl@126.comIntroduction: Neutrophil-to-lymphocyte ratio (NLR) is a marker of inflammation. This study aimed to evaluate the potential role of NLR to predict 90-day mortality.Methods: Data of 577 patients with burns over 30% of total body surface area were collected and retrospectively analyzed. The risk factors for 90-day mortality were evaluated using logistic regression analyses. Receiver operating characteristic (ROC) curve analysis of the 3rd day NLR was performed and the optimal cut-off value was calculated. The 90-day mortality rates were compared between high and low NLR groups using Kaplan-Meier analysis.Results: Age, mechanical ventilation, burn index, 3rd day NLR, and 7th day red blood cell and platelet (PLT) counts were found to be independent predictive values for 90-day mortality. In contrast, percentage of total body surface area burned, inhalation injury, 1st day white blood cell and neutrophil counts, the 3rd day lymphocytes and PLT counts, and 7th day hemoglobin level were not independently associated with 90-day mortality. The area under the ROC curve of the 3rd day NLR for severe burn–delayed death prediction was 0.665 (95% confidence interval, 0.591– 0.739), and the optimal cut-off value of the 3rd day NLR was 10.50. The 90-day mortality rates differed significantly between the NLR > 10.5 group and the NLR ≤ 10.5 group (17.03% vs 5.92%, respectively; P < 0.01).Conclusion: These results suggested that the 3rd day NLR was associated with an increased risk of death in severely burned patients; thus, it can provide useful information to predict 90-day mortality.Keywords: burns, neutrophil-to-lymphocyte ratio, 90-day mortality